2015
DOI: 10.1021/acs.est.5b02210
|View full text |Cite
|
Sign up to set email alerts
|

High-Gravity Carbonation Process for Enhancing CO2 Fixation and Utilization Exemplified by the Steelmaking Industry

Abstract: The high-gravity carbonation process for CO2 mineralization and product utilization as a green cement was evaluated using field operation data from the steelmaking industry. The effect of key operating factors, including rotation speed, liquid-to-solid ratio, gas flow rate, and slurry flow rate, on CO2 removal efficiency was studied. The results indicated that a maximal CO2 removal of 97.3% was achieved using basic oxygen furnace slag at a gas-to-slurry ratio of 40, with a capture capacity of 165 kg of CO2 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…Pang et al (2015) demonstrated that replacing non-carbonated slags with carbonated slags can result in a 20% increase in compressive strength in 28 days, as well as reduce environmental problems such as the leaching of heavy metals. A similar observation was made by Pan et al (2015c). This might be attributed to the enhanced hydration of C 3 A by CaCO 3 to form stable calcium carboaluminate (C 3 A·CaCO 3 ·11H), as described in Eq.…”
Section: Utilization Of Carbonated Product As Supplementary Cementitisupporting
confidence: 76%
See 2 more Smart Citations
“…Pang et al (2015) demonstrated that replacing non-carbonated slags with carbonated slags can result in a 20% increase in compressive strength in 28 days, as well as reduce environmental problems such as the leaching of heavy metals. A similar observation was made by Pan et al (2015c). This might be attributed to the enhanced hydration of C 3 A by CaCO 3 to form stable calcium carboaluminate (C 3 A·CaCO 3 ·11H), as described in Eq.…”
Section: Utilization Of Carbonated Product As Supplementary Cementitisupporting
confidence: 76%
“…High micro-mixing between the slurry and gas phases enhances the overall mass transfer, thereby improving the carbonation conversion and reducing the residence time. It was noted that energy consumption for the high-gravity carbonation process, including grinding, pumps, blowers, and rotation, was estimated to be 268.6 ± 57.9 kWh t-CO 2 -1 , with 90% CO 2 removal efficiency (Pan et al, 2015c), which met the goals set by the U.S. DOE (Matuszewski et al, 2011).…”
Section: Direct Carbonation: Energy Consumptionmentioning
confidence: 94%
See 1 more Smart Citation
“…This reaction is exothermic and faster than that of C 3 S hydration. 36 The unstable phase in eqn (13) aer one day would gradually convert to the monocarbonate phase and C 3 AH 6 , as shown in eqn (14). These reactions could enhance hydration heat and offer mechanical strength to the cement (especially for the initial strength development).…”
Section: Resultsmentioning
confidence: 99%
“…The highest carbonation conversion rate obtained is approximately 72% at a reaction time of 1 h, an operating pressure of 101 kPa, and a temperature of 60°C. Pan et al [18][19][20] investigated the accelerated carbonation of steelmaking slag coupled with metalworking wastewater in a rotating packed bed and high-gravity rotating packed bed reactor. Results showed that the applied rotating packed bed or high-gravity rotating packed bed reactor can improve the mass transfer rate among phases owing to its high centrifugal force and excellent micromixing ability, thereby achieving a superior CO 2 fixation efficiency.…”
Section: Introductionmentioning
confidence: 99%